Whoever you are...poster, c. 1985 (London, 1985)
1985 1980-95 "Whoever you are...poster, c. 1985" [BW0068], 1985, Trades Union Congress Trade union recruitment poster in several languages produced by the TUC South East Regional Council and the Joint Trade Union Committee on Racialism in the East End. Artist Dan Jones.